2017
DOI: 10.1103/physrevb.95.144418
|View full text |Cite
|
Sign up to set email alerts
|

Phase-separated magnetic ground state in Mn3Ga0.45Sn0.55C

Abstract: Existence of non-ergodic ground states is considered as a precursor to a first order long range magnetostructural transformation. Mn 3 Ga 0.45 Sn 0.55 C lies compositionally between two compounds, Mn 3 GaC and Mn 3 SnC, undergoing first order magnetic transformation. Mn 3 Ga 0.45 Sn 0.55 C though crystallizes in single phase cubic structure, exhibits more than one long range magnetic transitions.Using a combination of magnetization, ac susceptibility, neutron diffraction and XAFS techniques it is shown that, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
(20 reference statements)
1
13
0
Order By: Relevance
“…In particular, Mn-based antiperovskites exhibit interesting magnetic ordering properties and undergo various magnetic phase transitions. Among them, Mn 3 AC (A: Ga, In, Zn) undergo a multitude of complex magnetic transitions [9][10][11][12][13][14], and recently, it has been shown that the antiperovskite Mn 3 SnC stands out somewhat differently with its characteristic magnetic structure [15]. Mn 3 SnC undergoes a first-order magnetostructural transition near room temperature from a hightemperature paramagnetic (PM) state to a low-temperature, magnetically complex ordered state accompanied by a narrow thermal hysteresis.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Mn-based antiperovskites exhibit interesting magnetic ordering properties and undergo various magnetic phase transitions. Among them, Mn 3 AC (A: Ga, In, Zn) undergo a multitude of complex magnetic transitions [9][10][11][12][13][14], and recently, it has been shown that the antiperovskite Mn 3 SnC stands out somewhat differently with its characteristic magnetic structure [15]. Mn 3 SnC undergoes a first-order magnetostructural transition near room temperature from a hightemperature paramagnetic (PM) state to a low-temperature, magnetically complex ordered state accompanied by a narrow thermal hysteresis.…”
Section: Introductionmentioning
confidence: 99%
“…In magnetic cluster glasses, there are examples of materials exhibiting glassy characteristics and yet presenting long range magnetic order. Recently such a phenomenon has been explained to be due to presence of clusters large enough to show characteristics of long range magnetic order in neutron diffraction but still exhibit glassy behavior due to limited interaction between clusters [14]. Presence of such large strain domains separated by non martensitic regions in Ni 2 Mn 1.4 Fe 0.1 In 0.5 cannot be ruled out.…”
mentioning
confidence: 99%
“…It may also be seen that impurity phases of In and In 2 O 3 are also not detected from neutron diffraction. Unlike its Ga and Sn counterparts that exhibit pure magnetic reflections below their respective transition temperatures 12,16,26 , preliminary analysis of neutron diffraction data plotted in Fig. 3 (a) and (b) indicate no antiferromagnetic superlattice reflections at all temperatures down to 5 K. Instead, the presence of additional intensity in some of the low angle peaks confirms presence of long range ferromagnetic order in the compound.…”
Section: Resultsmentioning
confidence: 87%
“…As a result the magnetic propagation vector, k is 1 2 , 1 2 , 0 in Mn 3 SnC as against 1 2 , 1 2 , 1 2 in Mn 3 GaC 12 . The differences in the distortions of Mn 6 C octahedra are preserved even in the solid so-lutions of Mn 3 Ga 1−x Sn x C and result in lattice strain 15 as well as a cluster glassy ground state 16 . Such a non ergodic ground state in Mn 3 Ga 0.45 Sn 0.55 C was explained to be due to formation of Ga rich and Sn rich clusters in the compound.…”
Section: Introductionmentioning
confidence: 99%